2023
DOI: 10.3390/cancers15112964
|View full text |Cite
|
Sign up to set email alerts
|

Belantamab Mafodotin in Patients with Relapsed/Refractory Multiple Myeloma: Results of the Compassionate Use or the Expanded Access Program in Spain

Abstract: Belantamab-mafodotin (belamaf) is a novel antibody-drug conjugate targeting B-cell maturation antigen that showed anti-myeloma activity in patients with relapsed and refractory multiple myeloma (RRMM). We performed an observational, retrospective, and multicenter study aimed to assess the efficacy and safety of single-agent belamaf in 156 Spanish patients with RRMM. The median number of prior therapy lines was 5 (range, 1–10), and 88% of patients were triple-class refractory. Median follow-up was 10.9 months (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
2
7
1
Order By: Relevance
“…The survival outcomes were more favorable for the responders, most of whom had sustained disease control and long-term remission. Accumulating evidence from real-world studies is in accordance with our results (Table 2) [14][15][16][17][18][19]. A multicenter Italian study had a comparable cohort size (n = 28) to our study and reported an ORR of 40% and comparable survival outcomes [15].…”
Section: Discussionsupporting
confidence: 90%
“…The survival outcomes were more favorable for the responders, most of whom had sustained disease control and long-term remission. Accumulating evidence from real-world studies is in accordance with our results (Table 2) [14][15][16][17][18][19]. A multicenter Italian study had a comparable cohort size (n = 28) to our study and reported an ORR of 40% and comparable survival outcomes [15].…”
Section: Discussionsupporting
confidence: 90%
“…13 According to our analysis, most patients responded and improved their responses over the first few months of therapy, reaching VGPR/ CR. These results, which are superior to those reported in most prospective and retrospective real-world studies, 1,4,5,7,8,14,15 might reflect the decreased ocular toxicity achieved with our low-dose belantamab strategy, enabling continues treatment and deepening of response. These deep responses were translated into prolonged PFS.…”
Section: Discussioncontrasting
confidence: 51%
“…In the largest real-world series published to date, including 156 patients, ORR was 41.8% (4), translated into median progressionfree survival (PFS) and overall survival (OS) of 3.6 and 11.5 months, respectively. 4 Corneal event was common (87.9%; Grade ≥3, 33.7%) but their effect on treatment schedule was not reported. 4 In another real-world series of 106 patients, 5 ORR (45.5%), PFS, and OS (4.7 and 14.5 months, respectively) were similar, and most (55%) patients experienced dose delays.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…These include auristatins F, M and W, as well as monomethyl auristatin F (MMAF), PF-06380101, Duostatin 5 and keto-auristatin PE (KAPE). For example, MMAF was used in Belantamab mafodotin ADC for the treatment of relapsed or refractory myeloma [ 342 ]. Another Mafodotin-based ADC, Depatuxizumab mafodotin, targets EGFR in glioblastoma and EGFR-overexpressed tumors [ 343 ].…”
Section: Antibody and Peptide-mediated Delivery Of Michael Acceptorsmentioning
confidence: 99%